IS SHOE DROP A KEY FACTOR FOR INJURY PREVENTION IN RUNNING? PART 1: AN RCT ON INJURY RISK. Issue 4 (1st February 2017) - Malisoux, Laurent; Chambon, Nicolas; Urhausen, Axel; Theisen, Daniel
Abstract : Background: Modern running shoes come in variable heel-to-toe drops, but it is currently unknown if this feature plays a role in the prevention of injuries. Objective: To determine if the drop of conventional cushioned running shoes influences injury risk and whether running regularity (>6 months of regular practice over the previous year) modifies this association. Design: Double-blind randomised controlled trial, with a 6-month follow-up. Setting: Leisure-time distance runners. Participants: Study participants (n=553) were recruited via advertisements in local newspapers. They were required to report any running activity, sport practice and injury using a dedicated internet platform. Intervention: Running shoes with a drop of 10 mm (D10, n=176), 6 mm (D6, n=190) or 0 mm (D0, n=187). Apart from the shoe drop, the 3 versions were strictly identical. A stratified analysis was conducted according to the participants' running regularity. Main Outcome Measurements: First running-related injury self-reported by the participants, and systematically verified by email or phone call. Cox regression analyses were used to compare injury risk between exposure groups. Results: 136 of the participants (25%) sustained at least one injury. The proportion of injured participants were 21.6%, 27.4% and 24.6% in the D10, D6 and D0 groups, respectively. The overall injury risk was not different among the participants who had received the D6 version (hazard rate ratios – HR=1.30; 95% confidence intervals −95% CI=0.86–1.98) or the D0 version (HR=1.17; 95% CI=0.76–1.80) when compared to the conventional D10 version. The stratified analysis revealed that low drop shoes (D6 and D0 grouped together) were associated with a lower injury risk in occasional runners (HR=0.48; 95% CI=0.23–0.98), and with a higher injury risk in regular runners (HR=1.67; 95% CI=1.07–2.62). Conclusions: Overall, injury risk was not influenced by the drop of conventional cushioned running shoes, yet this association may be modified by the runner's profile.